EVALUATION OF ASSISTANCE FOR PREGNANT WOMEN THROUGH CONTINUOUS MIDWIFERY CARE WITH PREECLAMPSIA CASES IN SUMODIKARAN VILLAGE, DANDER DISTRICT, BOJONEGORO REGENCY - Azizah, Nur; Luluk, Sri; Utami, Rina; Irnawati, Prita Yuliana; Hidayah, Waqidil (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2022)
Pregnancy hypertension is a danger sign of pregnancy that significantly contributes to maternal and fetal morbidity and mortality. The purpose of the study was to evaluate the implementation of assistance for pregnant women through ongoing midwifery assistance in cases of hypertension during pregnancy to postpartum and family planning services. The research method uses a midwifery management approach and is documented in SOAP, the respondent is a pregnant woman GIP0A0 34 weeks of gestation, who is assisted and given midwifery care from pregnancy to family planning services in Sumodikaran Village, Dander District, Bojonegoro Regency. The results showed that midwifery care was carried out continuously and based on established standards of midwifery care. Pregnant women get services of at least 10 T, normal delivery care, postpartum and family planning services safely and in accordance with procedures. Mrs D as a respondent was given prenatal care according to a minimum standard of 10 T, during pregnancy NY D had hypertension but had already received treatment. Childbirth care was carried out at Aisyiyah Hospital, Bojonegoro, lasted 12 hours, the baby was born spontaneously at 9.30 p.m, cried strongly, reddish skin, active movement, good muscle tone, female, weight 3,000 g, body length 48 cm, Apgar Score: 8-9. Midwifery care during the puerperium was carried out 4 times (2 hours post partum while at Aisyiyah Hospital and 3 times home visits). Midwifery care for newborns is carried out immediately after the baby is born which is carried out at the hospital and carried out 3 times home visits. Midwifery care for post-partum contraceptive services is carried out on 40 days post partum. The mother plans to use a 3-month injectable family planning when her baby is 3 months old. In conclusion, evaluation of the implementation of assistance for pregnant women through continuous midwifery care in cases of hypertension during pregnancy to postpartum and family planning services after proper management is carried out, namely referral to health centers, pregnancy hypertension does not progress to preeclampsia. Maternity care, postpartum, newborn and family planning services are well implemented.